Current evidence on fast track cardiac recovery management. (16th January 2017) - Bainbridge, Daniel; Cheng, Davy
Abstract : This article reviews the evolution of current evidence on fast track cardiac recovery management in cardiac surgery, and particularly in minimally invasive and transcatheter aortic valve surgical procedure. The background of fast track cardiac surgery management and recovery in the 1990' with balanced anesthesia technique and early tracheal extubation is described. The safety, efficacy and cost benefits of fast track cardiac recovery are presented. The risk assessment of patients with severe aortic valve disease for minimally invasive or transcatheter surgical procedure is reviewed. The process of postoperative care together with the intraoperative anesthetic management is highlighted.